University Education in Nigeria: Challenges and Way Forward - Ajape Temitope Solomon; Ogunode Niyi Jacob; Deborah Jegede (Jurnal Sinestesia, 2020)
University education in Nigeria is the education that prepares the youths for future. University education is the key to the realization of the social, economic and technological advancement of a country. The Nigerian university education faces many problems. The researchers employed the used of secondary data to discuss the points raised in the article. This article identified poor planning, weak administration, inadequate funding, inadequate academic staff, inadequate infrastructural facilities, poor supervision, brain-drain, strike actions, corruption and poor research programme as the problems facing the university education in Nigeria. To address these challenges, the article recommendations include government should effective planning of universities education, appoint capable administrators, increase the funding of university education, provision of adequate infrastructural facilities, motivate the academic staff, implement agreement, fight the corruption in the university system and increase the funding of research programme.